(untitled) (International journal of medical sciences, 2026)
Breast milk is the biological gold standard in infant nutrition. This article discusses the biochemical and immunological properties of breast milk and its comparative analysis with NAN OPTIPRO 1 infant formula. The study analyzed the quantitative indicators of the main macro- and microelements, bioactive substances, immunoglobulins, fatty acids, vitamins and minerals of breast milk based on scientific sources. It was also shown that, despite the composition of the infant formula close to breast milk, the immunological activity is limited in terms of bioavailability. The article substantiates the importance of exclusive breastfeeding for 0-6 months and the need to use infant formula only on medical indications. The results obtained confirm that supporting breast milk and encouraging breastfeeding have important scientific and practical significance in maintaining the health of infants.